COUPLED FINITE ELEMENT ANALYSIS OF A DAM-RESERVOIR SYSTEM UNDER DYNAMIC LOADING (Journal of Engineering, 2008)
This investigation presents a coupled analysis of a dam-reservoir problem which includes all aspects of fluid-structure interaction (class I coupling) and soil-pore fluid–structure interaction (class II coupling) under earthquake excitations using the finite element method. The analysis involves the compressibility of water, the flexibility of the dam, the earthquake excitation, the structural damping and the material nonlinearity on the response. An efficient computer program in FORTRAN is developed for this analysis from the original computer code named MIXDYN. The new software for predicting and analyzing the coupled behaviour is established using the pressure formulation for modelling of fluid and the u-p formulation for modelling of soil-pore fluid behaviours. Also, the program prepared is provided with post-processing routines to plot the original and deformed meshes of the problem. A staggered partitioned solution technique for coupled field problems is implemented and used in the computer code. This scheme is incorporated in terms of sequential execution of single-field analyzers. The Drucker Prager model is used to simulate the behaviour of the soil and concrete. Implicit-Implicit Newmark’s scheme with a predictor-corrector algorithm is employed for time integration of the equations of motion. The capability and efficiency of the model are found to be very useful when applied on a dam-reservoir system.